Breast Cancer With Brain Metastases: Clinicopathologic Features, Survival, and Paired Biomarker Analysis. (23rd March 2015) - Shen, Qi; Sahin, Aysegul A.; Hess, Kenneth R.; Suki, Dima; Aldape, Kenneth D.; Sawaya, Raymond; Ibrahim, Nuhad K.
Abstract : Background: The aim of this study was to describe clinicopathologic features of patients with breast cancer brain metastasis (BCBM); to evaluate survival after diagnosis of BCBM; and to compare estrogen receptor (ER), progesterone receptor (PR), and HER2 expression in the paired primary and brain tumors. Materials and Methods: We identified 140 consecutive patients who underwent craniotomy for BCBM (either for diagnostic purpose or with therapeutic intent) at the University of Texas MD Anderson Cancer Center between 2002 and 2009. Results: Most patients had invasive ductal histology (91%), grade 3 tumors (67%), and positive axillary lymph node (64%). Of the tumors, 56% were ER‐negative, 62% were PR‐negative, 44% were HER2‐positive, and 28% were triple negative (TN). Brain metastasis (BM) was solitary in 51% of patients. Median interval from breast cancer diagnosis to BM was 46 months; median survival after BM was 14.1 months. In the univariate analysis, younger age, solitary brain metastasis, and ER or PR positivity in the breast tumors were associated with longer survival. There was a statistical trend toward increased survival in HER2‐positive patients compared with HER2‐negative patients (18 vs. 11 months). In the multivariate analysis, predictors for longer survival included younger age, solitary brain lesion, and HER2 positivity in the breast cancer. Biomarkers were evaluated in paired primary and brain tumors in 35 patients for ER status, 34 for PR status, and 36 for HER2 status. Discordant rates were 28% for ER, 20% for PR, and 3% for HER2. Conclusion: Compared with unselected breast cancer patients at the same institution, patients with breast cancer who had brain metastases had a higher proportion of hormone receptor‐negative, HER2‐positive, and TN tumors. Younger age, solitary brain lesion, and HER2 expression were independent predictors of better survival in patients with BCBM. HER2 status was highly concordant between the paired primary and brain tumors, whereas changes of ER and PR status occurred in a substantial proportion of the patients. These findings are important for making effective treatment decisions for patients with BCBM. Abstract : The aim of this study was to describe clinicopathologic features of patients with breast cancer brain metastasis (BCBM); to evaluate survival after diagnosis of BCBM; and to compare estrogen receptor, progesterone receptor, and HER2 expression in the paired primary and brain tumors. The results show that younger age, solitary brain lesion, and continuation of HER2‐targeted therapy in HER2‐positive BCBM patients are predictors of better survival.